A Modified Delphi Process to Prioritize Experiences and Guidance Related to ICU Restricted Visitation Policies During the Coronavirus Disease 2019 Pandemic. (25th October 2021) - Fiest, Kirsten M.; Krewulak, Karla D.; Makuk, Kira; Jaworska, Natalia; Hernández, Laura; Bagshaw, Sean M.; Burns, Karen E.; Cook, Deborah J.; Doig, Christopher J.; Fox-Robichaud, Alison; Fowler, Robert A.; Kho, Michelle E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To create evidence-based consensus statements for restricted ICU visitation policies to support critically ill patients, families, and healthcare professionals during current and future pandemics. DESIGN: Three rounds of a remote modified Delphi consensus process. SETTING: Online survey and virtual polling from February 2, 2021, to April 8, 2021. SUBJECTS: Stakeholders (patients, families, clinicians, researchers, allied health professionals, decision-makers) admitted to or working in Canadian ICUs during the coronavirus disease 2019 pandemic. MEASUREMENTS AND MAIN RESULTS: During Round 1, key stakeholders used a 9-point Likert scale to rate experiences (1—not significant, 9—significant impact on patients, families, healthcare professionals, or patient- and family-centered care) and strategies (1—not essential, 9—essential recommendation for inclusion in the development of restricted visitation policies) and used a free-text box to capture experiences/strategies we may have missed. Consensus was achieved if the median score was 7–9 or 1–3. During Round 2, participants used a 9-point Likert scale to re-rate experiences/strategies that did not meet consensus during Round 1 (median score of 4–6) and rate new items identified in Round 1. During Rounds 2 and 3, participants ranked items that reached consensus by order of importance (relative to other related items and experiences) using a weighted ranking system (0–100 points). Participants prioritized 11 experiences (e.g., variability of family's comfort with technology, healthcare professional moral distress) and developed 21 consensus statements (e.g., communicate policy changes to the hospital staff before the public, permit visitors at end-of-life regardless of coronavirus disease 2019 status, creating a clear definition for end-of-life) regarding restricted visitation policies. CONCLUSIONS: We have formulated evidence-informed consensus statements regarding restricted visitation policies informed by diverse stakeholders, which could enhance patient- and family-centered care during a pandemic.